The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/pr9081422
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Chip Formation Mechanisms in the Turning of Sintered ZnO Electro-Ceramics

Abstract: The sintered zinc oxide (ZnO) electro-ceramics are a brittle class of hard-to-cut materials such that shaping them with the post-finishing operations necessitates careful handling and precision machining. The conventional machining approach using the grinding and lapping processes represents limited productivity, an inability to produce the required geometries and frequent uncontrolled chipping of the edges of the final products. This study thus investigates the turning performance of dense sintered ZnO varist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
(76 reference statements)
2
4
0
Order By: Relevance
“…Mn doping reduced the mean ZnO grain size in all the ternary systems compared to undoped MOVs from ZnO-V2O5 systems, but the densification of the Mn3O4or MnO2-doped MOVs was almost equal, with a relative density (RD) of 94.6-96% of theoretical density (TD). These densities comply with the accepted values for commercial MOVs, with RD greater than 95% of TD, where TD is around 5.6-5.7 g/cm 3 [111].…”
Section: Structural Propertiessupporting
confidence: 88%
See 2 more Smart Citations
“…Mn doping reduced the mean ZnO grain size in all the ternary systems compared to undoped MOVs from ZnO-V2O5 systems, but the densification of the Mn3O4or MnO2-doped MOVs was almost equal, with a relative density (RD) of 94.6-96% of theoretical density (TD). These densities comply with the accepted values for commercial MOVs, with RD greater than 95% of TD, where TD is around 5.6-5.7 g/cm 3 [111].…”
Section: Structural Propertiessupporting
confidence: 88%
“…Additionally, the selected VFO and dopants [ 7 , 103 , 104 , 105 , 106 , 107 ] also play a crucial role. Furthermore, the techniques used for preparing MOV powder mixtures [ 108 , 109 ], as well as the consolidation (pressing of MOV powders) and densification techniques (sintering of MOV compacts) ( Figure 3 ), including post-annealing and post-processing techniques of MOVs [ 13 , 76 , 77 , 94 , 110 , 111 ], have a significant impact on the properties of MOVs.…”
Section: Overview Of the Development Of Zno-based Varistorsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, at feed rate v = 160 mm/min, the resultant slice roughness at the edges was trimmed down to 65 µm. This implies unsuitability of AWJ cutting at higher feed rates, as the edge regions and taper did not adhere to the principal electrical impulse testing requirements [30]. Further on, the comparison of surface roughness was also made by investigating the topographical color scans.…”
Section: Resultsmentioning
confidence: 99%
“…Before extensive study, preliminary experiments on turning of ZnO ceramics with PCD tools were performed and tool life, comparable to metal cutting was achieved. It was also concluded that the main factor reducing ZnO ceramics machinability is excessive machining-induced damage like grain pull-out and edge chipping [31]. A study using a conventional milling strategy, based on the turning parameters, yielding the best results, showed that surface microstructure can have a noteworthy impact on the machining characteristics of this material and substantially better surface roughness was achieved by abrasive waterjet machining [32].…”
Section: Machining Strategymentioning
confidence: 99%